Stable isotope ecology of terra preta in Caxiuanã National Forest, Brazil - Wright, David K.; Lima, Helena Pinto; Choi, Jungyu; Choi, Jeong-Heon; Browne Ribeiro, Anna T.; Mariano, Mayara C. P.; McDaniel, Kevin (Frontiers in Earth Science, 2023)
The Amazon Basin currently hosts the world's largest pool of terrestrial biodiversity and prior to European colonization of the Americas there were large human communities living in parkland ecosystems. We examine the formation of archaeological sites in the northeast sector of the Caxiuanã National Forest (CNF) using light stable isotopes of nitrogen and carbon, total carbon and nitrogen and Optically Stimulated Luminescence to characterize long-term human landscape management practices. We adopt a comparative approach, examining the formation processes of on-site (terra preta), near-site (terra marrom) and offsite (latosol) contexts. Previous research in the CNF has documented differences in pH, calcium, total organic carbon (TOC) and nitrogen (TN) between terra preta and terra marrom contexts as well as different forest structures based on remote sensing analysis. TOC and TN values obtained in our study augment and support previous research demonstrating significantly higher on-site values relative to near-site and off-site. However, the stable isotopes ( 13 C,  15 N) assayed from terra preta, terra marrom and latosols show statistically overlapping values, indicating the persistence of closed canopy in off-site and near-site contexts and the use of this canopy in the formation of on-site soils (terra preta). Our results corroborate the hypothesis that closed canopy ecosystems and human settlements persisted in the Amazon for thousands of years and formed the foundation of the region's rich biodiversity.